The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.31080/asnh.2020.04.0648
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidaemic and Antidiabetic Potency of Allium cepa (Onions) Bulb in Alloxan-Induced Diabetic Rats

Abstract: 60. Airaodion AI., et al. "Pharmacotherapeutic effect of methanolic extract of Telfairia occidentalis leaves on glycemic and lipidemic indexes of alloxan-induced diabetic rats".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
(44 reference statements)
0
10
0
Order By: Relevance
“…For this reason, scientists are looking at natural resources such as medicinal plants as alternative therapeutic agents against diabetes, as they are less harmful and have a lot of pharmacological value [ 98 , 99 ]. At present, many studies [ 97 , 98 , 100 ] are being performed on A. cepa to investigate its antidiabetic activities, and one of the experiments which was tested on diabetic rats showed that the aqueous extract of onions reduced blood glucose level in the same manner as that of glibenclamide, a conventional antidiabetic drug. The results also reported that the onion extracts contained kaempferol-3-O- β -D-6 ( P- coumaroyl) glucopyranoside which is responsible for the antidiabetic effect by promoting glucose uptake in rat soleus muscle [ 101 ].…”
Section: Therapeutic Potential Of Allium Cepamentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, scientists are looking at natural resources such as medicinal plants as alternative therapeutic agents against diabetes, as they are less harmful and have a lot of pharmacological value [ 98 , 99 ]. At present, many studies [ 97 , 98 , 100 ] are being performed on A. cepa to investigate its antidiabetic activities, and one of the experiments which was tested on diabetic rats showed that the aqueous extract of onions reduced blood glucose level in the same manner as that of glibenclamide, a conventional antidiabetic drug. The results also reported that the onion extracts contained kaempferol-3-O- β -D-6 ( P- coumaroyl) glucopyranoside which is responsible for the antidiabetic effect by promoting glucose uptake in rat soleus muscle [ 101 ].…”
Section: Therapeutic Potential Of Allium Cepamentioning
confidence: 99%
“…In addition, another experiment which was also conducted by Airaodion et al using the ethanol extract of onions found that the extract contained quercetin and rutin which stimulated glucose uptake in rat skeletal L6 myotubes by increasing GLUT-4 protein synthesis and its mobilization from the cytoplasm to the plasma membrane, as well as triggering the PI-3-K/Akt signaling pathway to regulate glucose transport [ 103 ]. Furthermore, in a study of six groups of alloxan-induced diabetic rats, three groups were treated with varying doses of A. cepa juice for 14 days, and the results found that the rats treated with onion juice had a markedly decreased blood glucose level than the rats who were not [ 100 ]. Jini and his group synthesized silver nanoparticles from A. cepa and an in vitro study was designed to evaluate those silver nanoparticles activity against diabetes.…”
Section: Therapeutic Potential Of Allium Cepamentioning
confidence: 99%
“…Given that a high HDLcholesterol/LDL-cholesterol ratio has been demonstrated to be advantageous and to be a sign of a lower risk of cardiovascular diseases, this likely explains why P. biglobosa may reduce the chance of developing heart ailments [49]. Two of the four major subgroups of plasma lipoproteins, HDL and LDL, are involved in lipid metabolism and the transfer of triglycerides, cholesterol, and cholesterol esters between tissues [50,51]. According to numerous studies, there is a negative correlation between plasma HDL cholesterol levels and the risk of cardiovascular disease, suggesting that HDL cholesterol has some protective effects against atherosclerosis [19,44].…”
Section: Legend: Tc = Total Cholesterol Tg = Triglyceride Hdl-c = Hig...mentioning
confidence: 99%
“…The protein elements needed to activate lipoprotein lipase, which releases fatty acids that can be oxidized by the -oxidation pathway to produce energy, are also provided by HDLcholesterol [50,51]. Most notably, because of its antioxidant property, HDL cholesterol can lessen the oxidation of LDL cholesterol and the atherogenic consequences of oxidized LDL cholesterol [57].…”
Section: Legend: Tc = Total Cholesterol Tg = Triglyceride Hdl-c = Hig...mentioning
confidence: 99%
“…Coronary heart disease (CHD) or cardiovascular diseases are recognized to be one of the most important reasons of morbidity and mortality and imposes tremendously heavy socio-economic burden worldwide. There are varieties of risk factors in the literature which increases the incidence of CHD such as hyperlipidemia [9][10][11]. CHD occurs when cholesterol accumulates on the artery walls, creating plaques.…”
Section: Introductionmentioning
confidence: 99%